ANALISIS PENILAIAN KONSUMEN PADA EKUITAS MEREK PRODUK HERBAL AYURWEDA PADA KONSUMEN DI KOTA DENPASAR - Ni Luh Adisti Abiyoga Wulandari; Ni Komang Sumadi; Mirah Ayu Trarintya (UNHI Press, 2019)
Ayurveda is one of the oldest holistic treatments in the world. Ayurveda herbal products have the potential to be developed as health products that have competitive advantages. Sustainable competitive advantage is done through strengthening brand equity, namely brand awareness, brand perceived quality, brand association, and brand loyalty. This research was conducted on consumers in the city of Denpasar, using 200 research respondents. Data collection is done by observation, interviews, questionnaires, and literature studies. The results showed that overall the respondents of the study both non-consumer respondents and consumer respondents had brand awareness, brand association, brand perceived quality, and good brand loyalty in Ayurveda herbal products. Where consumers' perceptions of brand awareness, brand association, brand perceived quality Ayurveda herbal products are higher than non-consumer respondents. In addition, the results of the analysis show that there are significant differences in brand association between consumers who have never consumed consumers who have consumed Ayurveda herbal products. While the perception of brand awareness and brand perceived quality did not show a significant difference in the two groups of respondents. Based on the results of these studies, developing brand equity of Ayurveda herbal products is very important to create competitive advantage. So that consumers are expected to prefer to use Ayurveda herbal products compared to other traditional medicines or modern / synthetic medical drugs that exist today.